Delayed Development of Head Control and Rolling in Infants With Tracheostomies - Shin, Hyun Iee; Shin, Hyung-Ik (Frontiers in Pediatrics, 2020)
Objective: Advances in neonatal care lead to an increased survival rate of critically ill babies. Infantile tracheostomies are not uncommon. However, only a few studies have addressed the effect of infant tracheostomy on early motor function. By comparing the scores of the Gross Motor Function Measure-88 (GMFM) on head control and rolling of infants with and without tracheostomies, the authors aimed to evaluate the effect of infanttracheostomy on early motor development. Methods: Medical records and the GMFM of subjects were retrospectively reviewed. Thirty-three infants with tracheostomies and 132 infants without tracheostomies were matched by gestational age, birth weight, and corrected age when the GMFM was performed using propensity score matching. GMFM scores in head control and rolling in different positions were compared by using generalized estimating equation (GEE). Results: Infants with tracheostomy showed lower values for head control in the supine position and in the pull to sit maneuver in multivariate GEE (p=0.008, 0.004, respectively). However, the results of head control in a prone position and head lift while the examiner held the thorax showed no difference between the groups. Rolling from prone to supine was delayed in the infants with tracheostomy (p= 0.002), while rolling from supine to prone was not delayed compared to the non-tracheostomized group. More than half (54%) of the tracheostomy group scored better in rolling from a prone to supine position than in head control in supine position, which was a higher ratio compared to the non-tracheostomy group (p=0.00). Conclusions: Tracheostomy seems to influence early motor development in infants. In particular, head control skills related to neck flexor muscle activation and rolling from prone to supine were delayed. Interventions may be required to facilitate these activities.